Amul's Lockdown Marketing Strategy - Bhalerao, Mrs. Harshali (RA Journal of Applied Research, 2021)
Mr. Michael Fernandes, creative man behind the Amul’s Butter Girl, was deep into thoughts. They just had a video conference meet with the other creative team to discuss on the upcoming strategy for promotion of Amul. The entire creative team had to meet virtually on account of the strict lockdown in the country due to the fast - spreading Covid 19 pandemic. Blue haired Amul butter girl had an enduring place on the billboards and on the hearts of the Indians. The Indians loved the Butter girl very much. Dr. Merian, Managing Director of Gujarat Cooperative Milk Marketing Federation (GCMMF) said that due to the current lockdown situation people would not be able to come on the streets looking at the billboards relishing the Amul advertisements for at least three months now. Or maybe more. At the same time ban on newspaper distribution would prevent the advertisements to reach homes of the Indian buyers. The major promotional media for Amul, billboards and newspapers would be useless during this lockdown period. This had set Michael worrying. He was just not getting a way out. How should he reach the minds of the Indians without Amul Butter girl advertisements on the billboard and in newspapers? How should he promote Amul brand during this lockdown condition?